miR-155-5p PROMOTES CD34+ APOPTOSIS AND INHIBITS BONE MARROW HEMATOPOIESIS IN MYELODYSPLASTIC SYNDROMES BY RAC1/CREB/MIR-15B AXIS - Cao, Meiwan; Peng, BaoLing; Xu, WanFu; Chen, PeiYu; Chen, Huan; Ye, LiPing; Xie, Jing; Wang, HongLi; Ren, Lu; Xiong, LiYa; Zhu, JingNan; Xu, XiangYe; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Myelodysplastic syndromes (MDS) are a group of heterogeneous myeloid clonal diseases that are characterized by ineffective bone marrow hematopoiesis. Since studies have confirmed the significance of miRNAs in ineffective hematopoiesis in MDS, the current report elucidated the mechanism mediated by miR-155-5p. The bone marrow of MDS patients was collected to detect miR-155-5p and to analyze the correlation between miR-155-5p and clinicopathological variables. Isolated bone marrow CD34+ cells were transfected with lentiviral plasmids that interfere with miR-155-5p, followed by apoptosis analysis. Finally, miR-155-5p-targeted regulation of RAC1 expression was identified, as well as the interaction between RAC1 and CREB, the co-localization of RAC1 and CREB, and the binding of CREB to miR-15b. As measured, miR-155-5p was upregulated in the bone marrow of MDS patients. Further cell experiments validated that miR-155-5p promoted CD34+ cell apoptosis. miR-155-5p could reduce the transcriptional activity of miR-15b by inhibiting RAC1, dissociating the interaction between RAC1 and CREB, and inhibiting the activation of CREB. Upregulating RAC1, CREB, or miR-15b could reduce miR-155-5p-mediated apoptosis promotion on CD34+ cells. Additionally, miR-155-5p could force PD-L1 expression, and this effect was impaired by elevating RAC1, CREB, or miR-15b. In conclusion, miR-155-5p mediates PD-L1-mediated apoptosis of CD34+ cells in MDS by RAC1/CREB/miR-15b axis, thereby inhibiting bone marrow hematopoiesis.